Modeling and prediction of the gradient retention data for ultrahigh performance liquid chromatography of benzodiazepines - Valigurová, Petra; Váňová, Jana; Česla, Petr (University of Pardubice, 2021)
This paper presents a method for prediction of the gradient retention times of six samples of benzodiazepines – phenazepam, pyrazolam, flubromazepam, meclonazepam, diclazepam, and diazepam. Isocratic and gradient separation of the compounds of interest was achieved on a Luna Omega C18 column followed by RP-LC/MS detection. The results have shown good agreement between the predicted and experimental retention data; however, higher differences were obtained for fast gradients in the ultrahigh performance separation mode.
Keywords: benzodiazepines; liquid chromatography; gradient elution; prediction of retention